2021
DOI: 10.1016/j.clnesp.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of nutritionally at-risk Coronavirus Disease 2019 (COVID 19) patients admitted in a tertiary government hospital: A follow-up study of the MalnutriCoV study

Abstract: Background and aims: The prevalence of malnutrition among adult Filipino patients with COVID 19 is 71.83%. Malnutrition has long been associated with poor outcomes among patients with pneumonia. This may be due to the increased risk of malnourished patients to develop impaired muscle and respiratory function. We aimed to determine the outcomes of adult COVID 19 patients admitted in a tertiary government hospital accordingly to nutrition status and risk. Methods: Retrospective study on the adult COVID 19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…This is concerning for both acute and more long-term COVID-19 outcomes. Recent research has shown that malnutrition prolongs hospitalization in COVID-19 patients by almost 12 days [ 24 , 25 ]. In addition, nutritional risk is associated with higher risk of developing severe COVID-19 infection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is concerning for both acute and more long-term COVID-19 outcomes. Recent research has shown that malnutrition prolongs hospitalization in COVID-19 patients by almost 12 days [ 24 , 25 ]. In addition, nutritional risk is associated with higher risk of developing severe COVID-19 infection [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that poor nutritional status was significantly associated with poor prognosis and high mortality. Similarly, previous studies showed that poor nutritional status is associated with a longer hospital stay, a higher rate of intensive care unit admission, and an increased mortality rate (Larrazabal et al, 2021;Nicolau et al, 2021). A retrospective study of 63 patients with COVID-19 hospitalized in China found that patients with higher NRS scores had higher white blood cell counts, lower lymphocyte counts, higher C-reactive protein and serum procalcitonin levels, severer COVID-19, and higher mortality rates (Y.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have shown that malnutrition is more prevalent in patients with COVID‐19, especially those in a critical state (Bedock et al, 2020; Wierdsma et al, 2021). Moreover, poor nutritional status is associated with a longer hospital stay, a higher rate of intensive care unit admission and an increased mortality rate (Larrazabal et al, 2021; Nicolau et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies published in the ESPEN-WHO Europe call have further confirmed and dissected this association. In non-ICU patients with COVID-19, poor nutritional state was associated with higher mortality in a systematic review [31] and with higher risk of transfer to ICU from hospital wards [30] as well as longer length of hospital stay [30,33], active complications at discharge [34], and ultimately negative outcomes and mortality in several studies and databases [29,30,34,35]. Specifically in geriatric settings, malnutrition risk at admission predicted hospital length of stay [27] while MNA-assessed malnutrition also predicted in-hospital mortality in a large population cohort [36].…”
Section: Malnutrition: Negative Clinical Impactmentioning
confidence: 99%